Progress and obstacles in the production and application of recombinant lignin-degrading peroxidases. Issue 3 (1st April 2016) - Lambertz, Camilla; Ece, Selin; Fischer, Rainer; Commandeur, Ulrich
ABSTRACT: Lignin is 1 of the 3 major components of lignocellulose. Its polymeric structure includes aromatic subunits that can be converted into high-value-added products, but this potential cannot yet been fully exploited because lignin is highly recalcitrant to degradation. Different approaches for the depolymerization of lignin have been tested, including pyrolysis, chemical oxidation, and hydrolysis under supercritical conditions. An additional strategy is the use of lignin-degrading enzymes, which imitates the natural degradation process. A versatile set of enzymes for lignin degradation has been identified, and research has focused on the production of recombinant enzymes in sufficient amounts to characterize their structure and reaction mechanisms. Enzymes have been analyzed individually and in combinations using artificial substrates, lignin model compounds, lignin and lignocellulose. Here we consider progress in the production of recombinant lignin-degrading peroxidases, the advantages and disadvantages of different expression hosts, and obstacles that must be overcome before such enzymes can be characterized and used for the industrial processing of lignin.